2010
DOI: 10.3382/ps.2010-813
|View full text |Cite
|
Sign up to set email alerts
|

Digestive tract measurements and histological adaptation in broiler lines divergently selected for digestive efficiency

Abstract: Two lines of broilers divergently selected for a high (D+) or a low (D-) AME(n) on a wheat-based diet were studied for morphological and histological characteristics of the digestive tract. A total of 630 birds of both lines were slaughtered after a 23-d feeding period. Digestive tract morphology and intestinal histology were investigated on a total of 24 birds to describe the consequences of divergent selection. Birds of the D+ line had 34% heavier gizzards (P < 0.001) and 22% heavier proventriculi than their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
80
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 25 publications
17
80
1
8
Order By: Relevance
“…Contrasting correlations in relative organ sizes have been discovered between lines selected for commercial objectives and high digestive efficiency (Carré et al 2005;Péron et al 2006;Rougière and Carré 2010;de Verdal et al 2010). For instance, Mussini (2012) showed that the gizzard is significantly smaller, and the pancreas similar, in modern commercial breeds when compared to old-type breeds fed on the same diet.…”
Section: Feed Intake Digestion and Absorptionmentioning
confidence: 99%
“…Contrasting correlations in relative organ sizes have been discovered between lines selected for commercial objectives and high digestive efficiency (Carré et al 2005;Péron et al 2006;Rougière and Carré 2010;de Verdal et al 2010). For instance, Mussini (2012) showed that the gizzard is significantly smaller, and the pancreas similar, in modern commercial breeds when compared to old-type breeds fed on the same diet.…”
Section: Feed Intake Digestion and Absorptionmentioning
confidence: 99%
“…et al, 2001). Differential development of the absorptive epithelium may be responsible for changes in absorption capacity of birds (Verdal et al, 2010). Available strains of broilers (eg.…”
Section: Introductionmentioning
confidence: 99%
“…According to Rougiere et al, (2009) andVerdal et al (2010), birds with larger gastric compartments (proventriculus and gizzard) tend to present more effective nutrient utilization compared with birds that show greater development of the small intestine. Thus, the higher energy use of slow-growing birds can be attributed to the peculiarities of the digestive organs of Isa Label broilers because they present with higher proventriculus and gizzard relative weight compared with Cobb broilers, as observed by Santos et al (2005).…”
Section: Values Of Metabolizable Energy and Metabolization Of Nutrienmentioning
confidence: 99%